Dracula - Stoker, Bram, 1847-1912 (Penguin readers. Level 3, 2019)
Classic / British English Count Dracula is a vampire. He drinks people’s blood. He lives in a lonely castle in the mountains of Transylvania. But then he comes to England and strange things start happening. People change. People become ill. Professor Van Helsing knows about vampires, but can he stop Count Dracula?